Brimato: One plant, dual benefits - Bahadur, Anant; Singh, Anish Kumar; Krishna, Hare; Kumar, Rajeev; Singh, Jagdish; Behera, Tusar Kanti (Indian Horticulture, 2023)
In view of ever-increasing demand for fresh produce in cities, peri-urban and urban farming may be promoted to reduce the dependency upon rural areas for supply of vegetables. In this direction, the dual grafting of brinjal and tomato on a single brinjal plant, termed as ‘Brimato’ (Brinjal + Tomato) has been developed first time and successfully demonstrated at ICAR-IIVR, Varanasi. This is an innovative grafting technology wherein both brinjal and tomato could be harvested from a single plant. Brimato has immense potential for large-scale adoption for production of homegrown fresh vegetables in urban and peri-urban areas, where space has always been a constraint.